A bio-based ionic complex with different oxidation states of phosphorus for reducing flammability and smoke release of epoxy resins. (February 2020) - Fang, Fang; Huo, Siqi; Shen, Haifeng; Ran, Shiya; Wang, Hao; Song, Pingan; Fang, Zhengping
Abstract: Developing high efficient, environmentally friendly and bio-based flame retardants for combustible polymers has gained increasing interest. Herein, a novel highly efficient biomass-derived flame retardant (EHPP@PA) with different oxidation state phosphorus is prepared via neutralization of phytic acid (PA) and phenylphosphonate-based compound (EHPP). Due to synergistic effect between PA and EHPP, the incorporation of EHPP@PA significantly improves the flame-retardant performances of epoxy resin (EP), bringing about 64% reduction in peak heat release rate (pHRR) and 16% reduction in total heat release (THR). Additionally, EP/EHPP@PA also displays excellent smoke suppression performance, exhibiting 45% reduction in peak CO production (pCOP), 61% reduction in peak smoke release production rate (pSPR), and 21% reduction in total smoke production (TSP). The flame-retardant mechanism of EHPP@PA is further investigated, indicating that EHPP@PA effectively exerts flame-retardant effect in the condensed and gaseous phases during combustion. In the condensed phase, phytic acid facilitates the formation of a protective char shield, while in the gas phase, EHPP releases PO· and NO· to quench active radicals and inhibits the combustion. Highlights: Adding 10 wt% of EHPP@PA reduces the peak heat release rate of epoxy resins by 64%. The peak smoke production rate of epoxy resins decreases by 61% in the presence of 10% of EHPP@PA. EHPP@PA improves flame retardancy of epoxy resins by working in the condensed and gas phases.